Memristive Behavior of NAOH-Immersed Titania Nanostructures - N. S. Kamarozaman; Z. Aznilinda; R.A. Bakar; S.H. Herman; M. Rusop (Journal of Mechanical Engineering and Sciences, 2013)
Memristive behavior is defined as a resistive switching loop which can be observed from the current-voltage (I-V) characteristic of a material. This paper reports the application of TiO2 (titania) nanostructures as an active layer for a memristive device instead of using titania thin film in nanoscale thickness as reported by other researchers. 60 nm thickness of titania thin film was deposited on ITO-coated glass substrate using the RF-magnetron sputtering method. Then, for the titania nanostructure’s growth, the TiO2/ITO/glass sample was immersed in 10 mol/l aqueous NaOH solution at 80°C while varying the immersion time for 30, 45 and 60 min. It was found that the sample immersed for 30 min showed better memristive behavior since larger switching loops were observed when positive bias was applied to the sample. The active layer consists of oxygen-deficient titania where oxygen vacancies might present on the surface of the thin film as the result of NaOH-immersion beside the formation of titania nanostructures. The degradation of the switching loops of the samples immersed in NaOH solution for 45 and 60 min might be due to the higher porosity of the samples resulting from the longer immersion process.